Recent advances in molecular mechanisms of acute kidney injury in patients with diabetes mellitus - Infante, Barbara; Conserva, Francesca; Pontrelli, Paola; Leo, Serena; Stasi, Alessandra; Fiorentino, Marco; Troise, Dario; dello Strologo, Andrea; Alfieri, Carlo; Gesualdo, Loreto; Castellano, Giuseppe; Stallone, Giovanni (Frontiers in Endocrinology, 2023)
Several insults can lead to acute kidney injury (AKI) in native kidney and transplant patients, with diabetes critically contributing as pivotal risk factor. High glucose per se can disrupt several signaling pathways within the kidney that, if not restored, can favor the instauration of mechanisms of maladaptive repair, altering kidney homeostasis and proper function. Diabetic kidneys frequently show reduced oxygenation, vascular damage and enhanced inflammatory response, features that increase the kidney vulnerability to hypoxia. Importantly, epidemiologic data shows that previous episodes of AKI increase susceptibility to diabetic kidney disease (DKD), and that patients with DKD and history of AKI have a generally worse prognosis compared to DKD patients without AKI; it is therefore crucial to monitor diabetic patients for AKI. In the present review, we will describe the causes that contribute to increased susceptibility to AKI in diabetes, with focus on the molecular mechanisms that occur during hyperglycemia and how these mechanisms expose the different types of resident renal cells to be more vulnerable to maladaptive repair during AKI (contrast- and drug-induced AKI). Finally, we will review the list of the existing candidate biomarkers of diagnosis and prognosis of AKI in patients with diabetes.